Strategi Nafkah Komunitas Petani Garam dalam Menghadapi Variabilitas Iklim di Gampong Cebrek Kabupaten Pidie: Livelihood Strategies of the Salt Farmer Community in Facing Climate Variability in Cebrek Village, Pidie Regency - Ibnu Phonna Nurdin; Khairulyadi Khairulyadi; Cut Lusi Chairunnisak; Dara Fatia (Jurnal Sosiologi Agama Indonesia (JSAI), 2023)
Climate variability in coastal regions presents significant challenges for salt farmer communities in their daily activities. This article aims to describe the impact of climate variability on salt farmer communities, as well as the livelihood strategy patterns they adopt in response to this variability. The study was conducted in Gampong Cebrek, Simpang Tiga Subdistrict, Pidie District, using qualitative methods. Data were collected through in-depth interviews and observations of specifically chosen salt farming communities. The findings indicate that these communities face difficult situations due to climate variability, including issues like flooding of fields during the rainy season, salt production difficulties, and vulnerable settlements. Adaptations include storing salt production soil in huts, raising the floor levels of homes and salt huts, and cleaning water channels. These challenges have led farmers to adopt strategies such as land intensification and extensification, livelihood diversification, and migration. Although these strategies are effective, migration, in particular, has negative impacts like the loss of future generations of salt farmers. Therefore, government support is needed to help salt farmer communities face the challenges of climate variability. AbstrakVariabilitas iklim di wilayah pesisir menyajikan tantangan signifikan bagi komunitas petani garam dalam menjalankan aktivitas harian mereka. Artikel ini bertujuan untuk mendeskripsikan terkait paparan variabilitas iklim pada komunitas petani garam serta pola strategi nafkah petani garam dalam menghadapi variabilitas iklim tersebut. Studi ini dilakukan di Gampong Cebrek, Kecamatan Simpang Tiga, Kabupaten Pidie, menggunakan metode kualitatif. Data dikumpulkan melalui wawancara mendalam dan observasi pada komunitas petani garam yang dipilih secara purposive. Temuan menunjukkan bahwa komunitas ini menghadapi situasi sulit akibat variabilitas iklim, dengan masalah seperti banjir di lahan saat musim hujan, kesulitan produksi garam, dan pemukiman yang rentan. Adaptasi yang dilakukan termasuk penyimpanan tanah produksi di pondok, peninggian lantai rumah dan pondok garam, serta pembersihan saluran air. Permasalahan ini mendorong petani mengembangkan strategi adaptasi, termasuk intensifikasi dan ekstensifikasi lahan, diversifikasi nafkah, dan migrasi. Meskipun strategi ini efektif, migrasi menimbulkan dampak negatif berupa hilangnya regenerasi petani garam. Oleh karena itu, diperlukan dukungan pemerintah untuk membantu komunitas petani garam menghadapi tantangan variabilitas iklim.